Analysis of consumer risk perception on online auction features - Mai Candra, Reski (2013)
This study examines consumer’s perception related to perceived risk while the doing transaction in e-auction system. Previous research found there are some features in e-auction system recognize as unclarity features since they indicate having fraud or cheating. In the online auction environment perception could be categories in two types such as privacy and security. This study proposed a conceptual model based on perceived risks from consumer’s investigation, associated directly with four cost features of e-auction system: payment method, auction fee, bidding fee and third party services that are combined with four perceived risk components: performance risk, psychological risk, financial risk, and time risk. Researcher has developed a questionnaire for collecting data from consumer’s who has experience in using e-auction. Through statistical analysis using regression, this study found that payment method, auction fee, bidding fee has a positive impact on perceived risk. However, third party services have a significant effect upon consumer perceived risk on financial risk but not significant effect to time risk. Furthermore the online auction features is directly related on reducing consumers' risk perception. In summarize, online auction features associated with financial plays a crucial role in reducing consumers' perceived risk in online auction transactions. The results of the study can offer insights to e-transaction and researchers of e-auction about the role of online auction system features in transaction and e-commerce.